Nilai Moral pada Dialog dalam Serial Anime "Naruto Shippuden": Analisis Semiotika Ferdinand De Saussure - Setiawan, Dani; Aditama, Dewa (Magenta | Official Journal STMK Trisakti, 2023)
Naruto is a manga series by Masashi Kishimoto which was adapted into an anime series. The Naruto manga tells the story of the life of the main character, Naruto Uzumaki, a hyperactive, cheerful, and ambitious ninja who wants to fulfill his desire to get the title of Hokage, the leader and strongest ninja in his village. Since childhood he was abandoned by his parents, so he never felt how the love of parents for their children. With the support of his friends and teachers, Naruto grows into a cheerful, optimistic and brave young man. Naruto is not only entertaining but also contains strong moral values about willpower, unyielding spirit, friendship, and mutual respect. In an era where many people experience pressure and difficulties, Naruto provides inspiration and valuable lessons on how to be strong and persistent in achieving dreams. This study aims to determine the meaning of markers and markers in scenes, dialogues and settings in the Naruto anime using descriptive methods and qualitative research types. Based on Ferdinand De Saussure’s semiotic theory analysis, there are representations of human values, moral values and meanings that can be drawn through scenes, dialogues and settings in Naruto. The moral values contained in this Naruto anime are (1) the importance of caring for others (2) understanding the suffering of fellow humans (3) Never give up and be consistent. This research was conducted so that the audience can better understand the values contained in the entertainment media they watch.